Thermal comfort assessment of UPM engineering library in tropical climate conditions - Fattahi, Arash; Sharaf, Hussein Kadhim; Mariah, Nor (Semarak Ilmu Publishing, 2024)
Thermal comfort is the study of indoor comfort level feel by the occupant in a room. This paper presents the study of thermal comfort that had been carried out in the library of engineering faculty at Universiti Putra Malayia in Serdang, Malaysia. The study was made in 4 days from 9 am to 11 am on October and November. This study was carried out to assess their thermal conditions during the occupants’ study hours. Thermal comfort variables were measured during study hours too. Qualitative and Quantitative data analysis showed that engineering library meet the requirement of comfort zone thermal conditions of ASHRAE standard 55 and ISO 7730. The result shows the environmental condition of the library is neutral to slightly warm in 4-point ASHRAE scale. The linear regression between Predicted Mean Vote and Operative Temperature reveals that the maximum acceptable temperature in this field of study is 26.5ºC.